2018
DOI: 10.1152/ajpcell.00234.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cell confluence regulates claudin-2 expression: possible role for ZO-1 and Rac

Abstract: Claudin-2 (Cldn-2) is a channel-forming tight junction (TJ) protein in the proximal tubules that mediates paracellular Na transport and has also emerged as a regulator of proliferation and migration. Expression of Cldn-2 is altered by numerous stimuli, but the underlying mechanisms remain incompletely understood. Here we show that Cldn-2 protein and mRNA expression were low in subconfluent tubular cells and increased during junction maturation. Cldn-1 or occludin did not exhibit similar confluence-dependence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 82 publications
6
24
2
Order By: Relevance
“…Previous studies have suggested that epithelial cell confluence is associated with morphology, polarity, and barrier function . Although changes in transepithelial electronic resistance have been reported to be minimal after cells reach confluence, we found that permeability decreased significantly when cells progressed from confluent to compact, with associated changes in height, suggesting changes in tight junction molecules .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have suggested that epithelial cell confluence is associated with morphology, polarity, and barrier function . Although changes in transepithelial electronic resistance have been reported to be minimal after cells reach confluence, we found that permeability decreased significantly when cells progressed from confluent to compact, with associated changes in height, suggesting changes in tight junction molecules .…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have suggested that epithelial cell confluence is associated with morphology, polarity, and barrier function . Although changes in transepithelial electronic resistance have been reported to be minimal after cells reach confluence, we found that permeability decreased significantly when cells progressed from confluent to compact, with associated changes in height, suggesting changes in tight junction molecules . These results demonstrate that compactness is required for an optimal barrier function, and suggest that confluence may be an intermediate rather than ultimate goal in the repair of an injured epithelial layer.…”
Section: Discussionsupporting
confidence: 43%
“…We found in this study that claudin-2 was increased in the URO-MCP-1 LPS-induced model for interstitial cystitis. In addition, IF images of the mouse bladder urothelial, obtained in this study, supports the notion that claudin-2 plays a role in the tight-junction network [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…The following antibodies against tight junction molecules were from Thermo/Invitrogen and have been validated earlier (19,69,90): claudin-2: monoclonal mouse antibody (catalog no. 325600) (used for Western blotting) and polyclonal rabbit antibody (catalog no.…”
Section: Materials and Antibodiesmentioning
confidence: 99%